2013
DOI: 10.1097/gme.0b013e318276c4cc
|View full text |Cite
|
Sign up to set email alerts
|

Conjugated equine estrogens and estradiol benzoate differentially modulate the natriuretic peptide system in spontaneously hypertensive rats

Abstract: These results indicate that estradiol and CEE have different effects on the reduction in body weight and blood pressure. These results are correlated with changes in plasma ANP levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…A two-way ANOVA of blood pressure levels revealed a main effect of strain (p < 0.0001) and steroid treatment (p < 0.01). However, the hypotensive effects of 17␤-estradiol may be explained only in part by down-regulation of AVP [69], because Firmes et al [83] recently reported that the decrease of blood pressure of SHR by 17␤-estradiol was associated to changes of several components of the natriuretic peptide system. In summary, hypertension under ovarian steroid deprivation could be due to several contributing factors [84], whereas estrogen-induced decrease of blood pressure may also involve several central and peripheral mediators.…”
Section: Effects Of 17␤-estradiol On Hypothalamic Arginine-vasopressi...mentioning
confidence: 99%
“…A two-way ANOVA of blood pressure levels revealed a main effect of strain (p < 0.0001) and steroid treatment (p < 0.01). However, the hypotensive effects of 17␤-estradiol may be explained only in part by down-regulation of AVP [69], because Firmes et al [83] recently reported that the decrease of blood pressure of SHR by 17␤-estradiol was associated to changes of several components of the natriuretic peptide system. In summary, hypertension under ovarian steroid deprivation could be due to several contributing factors [84], whereas estrogen-induced decrease of blood pressure may also involve several central and peripheral mediators.…”
Section: Effects Of 17␤-estradiol On Hypothalamic Arginine-vasopressi...mentioning
confidence: 99%
“…The influence of estrogens on the production and secretion of NPs has been well established in humans (5), rats (6) and mice (7). Estrogens act by stimulating the production and secretion of NPs; the levels of estrogen are low in ovariectomized (OVX) rats and mice (8) but are restored by 17β-estradiol administration (9-16).…”
Section: Introductionmentioning
confidence: 99%